Matrotrophic viviparity constrains microbiome acquisition during gestation in a live‐bearing cockroach, Diploptera punctata. Issue 18 (22nd August 2019) - Jennings, Emily C.; Korthauer, Matthew W.; Hamilton, Trinity L.; Benoit, Joshua B.
Abstract: The vertical transmission of microbes from mother to offspring is critical to the survival, development, and health of animals. Invertebrate systems offer unique opportunities to conduct studies on microbiome‐development‐reproduction dynamics since reproductive modes ranging from oviparity to multiple types of viviparity are found in these animals. One such invertebrate is the live‐bearing cockroach, Diploptera punctata . Females carry embryos in their brood sac, which acts as the functional equivalent of the uterus and placenta. In our study, 16S rRNA sequencing was used to characterize maternal and embryonic microbiomes as well as the development of the whole‐body microbiome across nymphal development. We identified 50 phyla and 121 classes overall and found that mothers and their developing embryos had significantly different microbial communities. Of particular interest is the notable lack of diversity in the embryonic microbiome, which is comprised exclusively of Blattabacteria, indicating microbial transmission of only this symbiont during gestation. Our analysis of postnatal development reveals that significant amounts of non‐Blattabacteria species are not able to colonize newborn D. punctata until melanization, after which the microbial community rapidly and dynamically diversifies. While the role of these microbes during development has not been characterized, Blattabacteria must serve a critical role providing specific micronutrients lacking in milk secretions to the embryos during gestation. This research provides insight into the microbiome development, specifically with relation to viviparity, provisioning of milk‐like secretions, and mother–offspring interactions during pregnancy. Abstract : Invertebrate systems offer unique opportunities to conduct studies on microbiome‐development‐reproduction dynamics since reproductive modes ranging from oviparity to multiple types of viviparity are found in these animals. One such invertebrate is the live‐bearing cockroach, and Diploptera punctata 16S rRNA sequencing was used to characterize the D. punctata maternal and embryonic microbiomes as well as the development of the whole‐body microbiome across nymphal development, identifying 50 phyla and 121 classes overall and found that symbionts are not transmitted to offspring during pregnancy, rather the microbiome is acquired during the first instar stage.